Assessing the health risks of reintroduction: The example of the Amur leopard, Panthera pardus orientalis. Issue 3 (29th December 2019) - Lewis, John; Tomlinson, Alex; Gilbert, Martin; Alshinetski, Mikhail; Arzhanova, Tanya; Goncharuk, Mikhail; Goodrich, John; Kerley, Linda; Korotkova, Irina; Miquelle, Dale; Naidenko, Sergey; Sulikhan, Nadezhda; et al.
Abstract: Translocation of wildlife as a means of reintroducing or reinforcing threatened populations is an important conservation tool but carries health risks for the translocated animals and their progeny, as well as wildlife, domestic animals and humans in the release area. Disease risk analyses (DRA) are used to identify, prioritize and design mitigation strategies to address these threats. Here, we use a DRA undertaken for Amur leopards ( Panthera pardus orientalis ) to illustrate how specific methodology can optimize mitigation strategy design. A literature review identified a total of 98 infectious hazards and 28 non‐infectious hazards. Separate analyses were undertaken for disease risks in leopards from hazards of source origin (captive zoo collections and the transit pathway to the Russian Far East), or of destination origin (in breeding enclosures and wider release areas); and for disease risks in other wildlife, domesticated species or humans, similarly from hazards of source or destination origin . Hazards were assessed and ranked as priority 1, priority 2, priority 3 or low priority in each of the defined scenarios. In addition, we undertook a generic assessment of stress on individual leopards. We use three examples to illustrate the process: Chlamydophila felis, canine distemper virus (CDV) and feline immunodeficiency virus (FIV). We found that many potentially expensive screening procedures could be performed prior to export of leopards, putting the onus of responsibility onto the zoo sector, for which access to diagnostic testing facilities is likely to be optimal. We discuss how our methods highlighted significant data gaps relating to pathogen prevalence in the Russian Far East and likely future unpredictability, in particular with respect to CDV. There was emphasis at all stages on record keeping, meticulous planning, design, staff training and enclosure management, which are relatively financially inexpensive. Actions to minimize stress featured at all time points in the strategy and also focussed on planning, design and management.